On the relationship between knowledge creation and economic performance - Vila, Luis E.; Cabrer, Bernardí; Pavía, Jose M. (Technological and Economic Development of Economy, 2015)
An empirical two-equation dynamic panel-data model system with fixed effects is proposed to analyze the relationship between knowledge creation and economic performance across regions over time. Estimates of the model for Spanish regions show that (i) knowledge creation depends on local R&D effort, on the amount of knowledge in use, and on knowledge creation in neighboring regions; and (ii) assimilation of new knowledge depends on local knowledge creation and on assimilation of knowledge in neighboring regions. Both processes include region-specific context fixed effects and region-specific time effects, representing region-specific dynamic influences. The results imply that (a) efficiency gains at regional level may be achieved by investing locally in the creation of new knowledge, either technological or organizational; (b) creation of knowledge in a region may be promoted by using greater amounts of already existing knowledge, as well as by increasing local R&D effort; (c) both knowledge creation and knowledge assimilation spread to/from neighboring regions; and (d) regional contexts influence both knowledge creation and knowledge assimilation separately.First published online: 05 Feb 2014